2006
DOI: 10.1093/ps/85.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic growth promoters on broiler performance, intestinal growth parameters, and quantitative morphology

Abstract: The effects of addition of bacitracin methylene disalicylate (BMD) or virginiamycin (VM) to a corn-soybean meal diet on broiler performance and gastrointestinal tract (GIT) growth parameters and morphology were studied at various ages during growth and finishing. Male and female birds were killed at 1, 3, 5, or 7 wk of age for gross and histologic examination of the duodenum and ileum. Feeding either antibiotic increased BW and decreased intestinal length and weight at all times compared with control birds. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
131
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(174 citation statements)
references
References 31 publications
19
131
1
9
Order By: Relevance
“…But, as reported previously, narrow or thinner villous width, as observed in T1, does not necessarily mean that they are susceptible to breakage, resulting in contamination of carcasses during processing (Miles et al, 2006). In T1 birds, however, the antibiotic effect may not be ruled out in reducing villi properties.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…But, as reported previously, narrow or thinner villous width, as observed in T1, does not necessarily mean that they are susceptible to breakage, resulting in contamination of carcasses during processing (Miles et al, 2006). In T1 birds, however, the antibiotic effect may not be ruled out in reducing villi properties.…”
Section: Resultsmentioning
confidence: 59%
“…In T1 birds, however, the antibiotic effect may not be ruled out in reducing villi properties. Miles et al (2006) reported the smallest total villous area and shortest villous height and crypt depth in the ileum of chicks that were supplemented with the antibiotic virginiamycin. On the other hand, M. oleifera leaves contain glutathione, a conjugate element of glutamate, the most abundant amino acid in blood, which plays a vital role in maintaining mucosal integrity (Rao & Samak, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Deeper crypts are indicative of rapid tissue turnover in order to permit renewal of villi and normal sloughing or pathogenic invasion resulting in inflammation (Miles et al, 2006). Long villi and shallow crypts provide a larger surface area for the absorption of nutrients and low renewal rate, allowing efficient enzyme production and maturation of the intestinal cells (Yang et al, 2009).…”
Section: Gut Morphologymentioning
confidence: 99%
“…Benefits of the inclusion of AGP in broiler diets on live performance have long been demonstrated (Miles et al, 2006;Cervantes et al, 2008;Hossain et al, 2008;Demir et al, 2008;Vieira et al, 2010). The mechanism of action of these compounds, however, is not easily explained.…”
Section: Resultsmentioning
confidence: 99%